Corrigendum to “Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage” [For. Ecol. Manage. 1 – May 27, 2026] - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Soil organic carbon sequestration over 50 years in resampled afforestation chronosequences on former cropland - Ming Yu; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Teresa G. Bárcena; Inger Kappel Schmidt; Per Gundersen; Ludovica D'Imperio; Carsten W. Mueller; Lars Vesterdal (Journal of Environmental Management, 2026)

Understory vegetation development along 60-year chronosequences of oak, beech, and Norway spruce - Davide Barsotti; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; Inger Kappel Schmidt (Forest Ecology and Management, 2026)

Drivers of Deposited Nitrogen Retention and Its Contribution to Carbon Sequestration in Chinese Forests - Geshere Abdisa Gurmesa; Ang Wang; Shanlong Li; Feifei Zhu; Kai Huang; Yihang Duan; Qinggong Mao; Quan Zhi; Ronghua Kang; Per Gundersen; Weixing Zhu; Yunting Fang (Global Change Biology, 2026)
Anthropogenic nitrogen (N) deposition alters forest functioning and their capacity to sequester carbon (C), yet its contribution to the forest C sink depends on N retention and allocation between plant biomass and soil pools. Despite high N deposition across China, the magnitude and drivers of N retention and contribution to forest C sequestration remain unclear due to a lack of systematic regional synthesis. Here, we synthesized data from decades of 15 N tracer experiments spanning boreal to tropical regions of China to quantify the retention of deposited N, distribution among plant and soil pools, and contribution to forest C sequestration. On average, Chinese forests retained ~65% of the deposited N, with about two‐thirds stored in the soil. Total retention and partitioning of N varied with climate, successional stage, and N forms. Soil organic layer retention declined, while mineral soil retention increased along a north–south gradient in mean annual temperature. Chronically N‐saturated and disturbed forests exhibited low plant retention, whereas other forests showed substantial uptake across climate zones. Total ecosystem retention efficiency generally declined from boreal to tropical forests. Across successional stages, retention did not differ significantly; however, primary forests retained more deposited N in mineral soils, whereas plantations favored retention in the organic layer. Stoichiometric scaling indicates that CN response (kg C sequestered per kg deposited N) varies among forest types, ranging from ~7 to 40 kg C kg −1 N, with boreal forests and plantations exhibiting the strongest C response due to greater N limitation. This suggests that over the past decade, N deposition enhanced C sequestration by approximately 0.11 Pg C year −1 , accounting for 20%–30% of China's forest C sink. Overall, these findings advance understanding of the drivers of deposited N retention and its contribution to C sequestration, with implications for predicting forest N and C dynamics under global change.

Structural diversity, tree species richness and biomass production in new forests on agricultural land - Yamina M. Rosas; Inger Kappel Schmidt; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; David Bille Byriel; Mathias Just Justesen; Davide Barsotti; Sebastian Kepfer-Rojas (Remote Sensing of Environment, 2025)

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Higher resistance of larch-broadleaf mixed forests than larch forests against soil acidification under experimental nitrogen addition - Meixia Gao; Guigang Lin; Feifei Zhu; Zhou Wu; Per Gundersen; De-Hui Zeng; Erik A. Hobbie; Weixing Zhu; Yunting Fang (Plant and Soil, 2024)

Co-creating coastal sustainability goals and indicators - Sigrid Engen; Vera Helene Hausner; Eirik Mikkelsen; Hege Gundersen; Hartvig Christie; Jannike Falk-Andersson; Benjamin S. Halpern; Per Fauchald (Sustainability Science, 2024)
Indicators can be powerful tools to measure progress towards achieving societal goals, and many indicators have been developed for sustainability goals nationally and internationally. When indicators are developed solely through top-down approaches without engaging local knowledge, they often fall short of capturing local perceptions and concerns relevant to decision-making. The aim of this project was to co-create a Coastal Barometer and its component indicators, together with local knowledge-holders and communities, using the Ocean Health Index as a framework. As a first step, local knowledge-holders from six communities dispersed across Northern Norway were invited to articulate local sustainability goals and the required knowledge for eight broad topics pertaining to global OHI goals: small-scale fisheries, food production, sense of place, tourism, food production, clean waters, carbon storage and economy and livelihoods. In this paper, our main focus is the co-design phase of the Coastal Barometer, namely eliciting sustainability goals. We thus, present locally desired sustainability goals and sub-goals and the process of eliciting these goals. We also include suggestions from local knowledge-holders on how to reach these goals (i.e. proposed management measures), along with researchers’ assessment of data availability (part of the co-production process) for developing indicators to measure progress towards these goals. Finally, we discuss the benefits and challenges of co-developing sustainability goals and indicators with local knowledge-holders. We conclude that co-design can increase the quality of sustainability assessments by enriching the view of coastal sustainability. This knowledge can subsequently be used to align indicators with local sustainability goals as well as to the local context where the indicators will be applied.

Unexpected high retention of 15 N‐labeled nitrogen in a tropical legume forest under long‐term nitrogen enrichment - Jinhua Mao; Qinggong Mao; Per Gundersen; Geshere A. Gurmesa; Wei Zhang; Juan Huang; Senhao Wang; Andi Li; Yufang Wang; Yabing Guo; Rongzhen Liu; Jiangming Mo; et al. (Global Change Biology, 2022)
The responses of forests to nitrogen (N) deposition largely depend on the fates of deposited N within the ecosystem. Nitrogen‐fixing legume trees widely occur in terrestrial forests, but the fates of deposited N in legume‐dominated forests remain unclear, which limit a global evaluation of N deposition impacts and feedbacks on carbon sequestration. Here, we performed the first ecosystem‐scale 15 N labeling experiment in a typical legume‐dominated forest as well as in a nearby non‐legume forest to determine the fates of N deposition between two different forest types and to explore their underlying mechanisms. The 15 N was sprayed bimonthly for 1 year to the forest floor in control and N addition (50 kg N ha −1 year −1 for 10 years) plots in both forests. We unexpectedly found a strong capacity of the legume forest to retain deposited N, with 75 ± 5% labeled N recovered in plants and soils, which was higher than that in the non‐legume forest (56 ± 4%). The higher 15 N recovery in legume forest was mainly driven by uptake by the legume trees, in which 15 N recovery was approximately 15% more than that in the nearby non‐legume trees. This indicates higher N‐demand by the legume than non‐legume trees. Mineral soil was the major sink for deposited N, with 39 ± 4% and 34 ± 3% labeled N retained in the legume and non‐legume forests, respectively. Moreover, N addition did not significantly change the 15 N recovery patterns of both forests. Overall, these findings indicate that legume‐dominated forests act as a strong sink for deposited N regardless of high soil N availability under long‐term atmospheric N deposition, which suggest a necessity to incorporate legume‐dominated forests into N‐cycling models of Earth systems to improve the understanding and prediction of terrestrial N budgets and the global N deposition effects.

Dynamics and multi‐annual fate of atmospherically deposited nitrogen in montane tropical forests - Ang Wang; Dexiang Chen; Oliver L. Phillips; Per Gundersen; Xulun Zhou; Geshere A. Gurmesa; Shanlong Li; Weixing Zhu; Erik A. Hobbie; Xueyan Wang; Yunting Fang (Global Change Biology, 2021)
The effects of nitrogen (N) deposition on forests largely depend on its fate after entering the ecosystem. While several studies have addressed the forest fate of N deposition using 15 N tracers, the long‐term fate and redistribution of deposited N in tropical forests remains unknown. Here, we applied 15 N tracers to examine the fates of deposited ammonium ( ) and nitrate ( ) separately over 3 years in a primary and a secondary tropical montane forest in southern China. Three months after 15 N tracer addition, over 60% of 15 N was retained in the forests studied. Total ecosystem retention did not change over the study period, but between 3 months and 3 years following deposition 15 N recovery in plants increased from 10% to 19% and 13% to 22% in the primary and secondary forests, respectively, while 15 N recovery in the organic soil declined from 16% to 2% and 9% to 2%. Mineral soil retained 50% and 35% of 15 N in the primary and secondary forests, with retention being stable over time. The total ecosystem retention of the two N forms did not differ significantly, but plants retained more than and the organic soil more than . Mineral soil did not differ in and retention. Compared to temperate forests, proportionally more 15 N was distributed to mineral soil and plants in these tropical forests. Overall, our results suggest that atmospherically deposited and is rapidly lost in the short term (months) but thereafter securely retained within the ecosystem, with retained N becoming redistributed to plants and mineral soil from the organic soil. This long‐term N retention may benefit tropical montane forest growth and enhance ecosystem carbon sequestration.

Correction to: Vertical Redistribution of Soil Organic Carbon Pools After Twenty Years of Nitrogen Addition in Two Temperate Coniferous Forests - Stefan J. Forstner; Viktoria Wechselberger; Stefanie Müller; Katharina M. Keiblinger; Eugenio Díaz-Pinés; Wolfgang Wanek; Patrick Schleppi; Frank Hagedorn; Per Gundersen; Michael Tatzber; Martin H. Gerzabek; Sophie Zechmeister-Boltenstern (Ecosystems, 2019)

Vertical Redistribution of Soil Organic Carbon Pools After Twenty Years of Nitrogen Addition in Two Temperate Coniferous Forests - Stefan J. Forstner; Viktoria Wechselberger; Stefanie Müller; Katharina M. Keibinger; Eugenio Díaz-Pinés; Wolfgang Wanek; Patrick Scheppi; Frank Hagedorn; Per Gundersen; Michael Tatzber; Martin H. Gerzabek; Sophie Zechmeister-Boltenstern (Ecosystems, 2019)

High retention of 15 N‐labeled nitrogen deposition in a nitrogen saturated old‐growth tropical forest - Geshere Abdisa Gurmesa; Xiankai Lu; Per Gundersen; Qinggong Mao; Kaijun Zhou; Yunting Fang; Jiangming Mo (Global Change Biology, 2016)
The effects of increased reactive nitrogen (N) deposition in forests depend largely on its fate in the ecosystems. However, our knowledge on the fates of deposited N in tropical forest ecosystems and its retention mechanisms is limited. Here, we report the results from the first whole ecosystem 15 N labeling experiment performed in a N‐rich old‐growth tropical forest in southern China. We added 15 N tracer monthly as 15 NH 4 15 NO 3 for 1 year to control plots and to N‐fertilized plots (N‐plots, receiving additions of 50 kg N ha −1 yr −1 for 10 years). Tracer recoveries in major ecosystem compartments were quantified 4 months after the last addition. Tracer recoveries in soil solution were monitored monthly to quantify leaching losses. Total tracer recovery in plant and soil (N retention) in the control plots was 72% and similar to those observed in temperate forests. The retention decreased to 52% in the N‐plots. Soil was the dominant sink, retaining 37% and 28% of the labeled N input in the control and N‐plots, respectively. Leaching below 20 cm was 50 kg N ha −1 yr −1 in the control plots and was close to the N input (51 kg N ha −1 yr −1 ), indicating N saturation of the top soil. Nitrogen addition increased N leaching to 73 kg N ha −1 yr −1 . However, of these only 7 and 23 kg N ha −1 yr −1 in the control and N‐plots, respectively, originated from the labeled N input. Our findings indicate that deposited N, like in temperate forests, is largely incorporated into plant and soil pools in the short term, although the forest is N‐saturated, but high cycling rates may later release the N for leaching and/or gaseous loss. Thus, N cycling rates rather than short‐term N retention represent the main difference between temperate forests and the studied tropical forest.

Afforestation effects on SOC in former cropland: oak and spruce chronosequences resampled after 13 years - Teresa G. Bárcena; Per Gundersen; Lars Vesterdal (Global Change Biology, 2014)
Chronosequences are commonly used to assess soil organic carbon ( SOC ) sequestration after land‐use change, but SOC dynamics predicted by this space‐for‐time substitution approach have rarely been validated by resampling. We conducted a combined chronosequence/resampling study in a former cropland area (Vestskoven) afforested with oak ( Quercus robur ) and Norway spruce ( Picea abies ) over the past 40 years. The aims of this study were (i) to compare present and previous chronosequence trends in forest floor and top mineral soil (0–25 cm) C stocks; (ii) to compare chronosequence estimates with current rates of C stock change based on resampling at the stand level; (iii) to estimate SOC changes in the subsoil (25–50 cm); and (iv) to assess the influence of two tree species on SOC dynamics. The two chronosequence trajectories for forest floor C stocks revealed consistently higher rates of C sequestration in spruce than oak. The chronosequence trajectory was validated by resampling and current rates of forest floor C sequestration decreased with stand age. Chronosequence trends in topsoil SOC in 2011 did not differ significantly from those reported in 1998, however, there was a shift from a negative rate (1998: −0.3 Mg C ha −1 yr −1 ) to no change in 2011. In contrast SOC stocks in the subsoil increased with stand age, however, not significantly ( P = 0.1), suggesting different C dynamics in and below the former plough layer. Current rates of C change estimated by repeated sampling decreased with stand age in forest floors but increased in the topsoil. The contrasting temporal change in forest floor and mineral soil C sequestration rates indicate a shift in C source‐sink strength after approximately 40 years. We conclude that afforestation of former cropland within the temperate region may induce soil C loss during the first decades followed by a recovery phase of yet unknown duration.

The natural abundance of 15N in litter and soil profiles under six temperate tree species: N cycling depends on tree species traits and site fertility - Ingeborg Callesen; Lars Ola Nilsson; Inger Kappel Schmidt; Lars Vesterdal; Per Ambus; Jesper Riis Christiansen; Peter Högberg; Per Gundersen (Plant and Soil, 2013)

Changes in microbial activities and biomasses over a forest floor gradient in C-to-N ratio - Lars Ola Nilsson; Håkan Wallander; Per Gundersen (Plant and Soil, 2012)

Environmental Services Provided from Riparian Forests in the Nordic Countries - Per Gundersen; Ari Laurén; Leena Finér; Eva Ring; Harri Koivusalo; Magne Sætersdal; Jan-Olov Weslien; Bjarni D. Sigurdsson; Lars Högbom; Jukka Laine; Karin Hansen (Ambio, 2010)

Role of six European tree species and land‐use legacy for nitrogen and water budgets in forests - JESPER RIIS CHRISTIANSEN; LARS VESTERDAL; INGEBORG CALLESEN; BO ELBERLING; INGER KAPPEL SCHMIDT; PER GUNDERSEN (Global Change Biology, 2010)
Water and nutrient fluxes for single stands of different tree species have been reported in numerous studies, but comparative studies of nutrient and hydrological budgets of common European deciduous tree species are rare. Annual fluxes of water and inorganic nitrogen (N) were established in a 30‐year‐old common garden design with stands of common ash ( Fraxinus excelsior ), European beech ( Fagus sylvatica L.), pedunculate oak ( Quercus robur ), small‐leaved lime ( Tilia cordata Mill.), sycamore maple ( Acer pseudoplatanus ) and Norway spruce ( Picea abies [L.] Karst .) replicated at two sites in Denmark, Mattrup and Vallø during 2 years. Mean annual percolation below the root zone (mm yr −1 ±SE, n =4) ranked in the following order: maple (351±38)>lime (284±32), oak (271±25), beech (257±30), ash (307±69)≫ spruce (75±24). There were few significant tree species effects on N fluxes. However, the annual mean N throughfall flux (kg N ha −1 yr −1 ±SE, n =4) for spruce (28±2) was significantly larger than for maple (12±1), beech (11±1) and oak (9±1) stands but not different from that of lime (15±3). Ash had a low mean annual inorganic N throughfall deposition of 9.1 kg ha −1 , but was only present at Mattrup. Annual mean of inorganic N leaching (kg ha −1 yr −1 ±SE, n =4) did not differ significantly between species despite of contrasting tree species mean values; beech (25±9)>oak (16±10), spruce (15±8), lime (14±8)≫ maple (1.9±1), ash (2.0±1). The two sites had similar throughfall N fluxes, whereas the annual leaching of N was significantly higher at Mattrup than at Vallø. Accordingly, the sites differed in soil properties in relation to rates and dynamics of N cycling. We conclude that tree species affect the N cycle differently but the legacy of land use exerted a dominant control on the N cycle within the short‐term perspective (30 years) of these stands.

Soil–atmosphere exchange of N2O, CO2 and CH4 along a slope of an evergreen broad-leaved forest in southern China - Yunting Fang; Per Gundersen; Wei Zhang; Guoyi Zhou; Jesper Riis Christiansen; Jiangming Mo; Shaofeng Dong; Tao Zhang (Plant and Soil, 2009)

Large Loss of Dissolved Organic Nitrogen from Nitrogen-Saturated Forests in Subtropical China - Yunting Fang; Weixing Zhu; Per Gundersen; Jiangming Mo; Guoyi Zhou; Muneoki Yoh (Ecosystems, 2009)

Seedling growth response of two tropical tree species to nitrogen deposition in southern China - Jiangming Mo; Dejun Li; Per Gundersen (European Journal of Forest Research, 2008)

Nitrogen addition reduces soil respiration in a mature tropical forest in southern China - JIANGMING MO; WEI ZHANG; WEIXING ZHU; PER GUNDERSEN; YUNTING FANG; DEJUN LI; HUI WANG (Global Change Biology, 2008)
Response of soil respiration (CO 2 emission) to simulated nitrogen (N) deposition in a mature tropical forest in southern China was studied from October 2005 to September 2006. The objective was to test the hypothesis that N addition would reduce soil respiration in N saturated tropical forests. Static chamber and gas chromatography techniques were used to quantify the soil respiration, following four‐levels of N treatments (Control, no N addition; Low‐N, 5 g N m −2 yr −1 ; Medium‐N, 10 g N m −2 yr −1 ; and High‐N, 15 g N m −2 yr −1 experimental inputs), which had been applied for 26 months before and continued throughout the respiration measurement period. Results showed that soil respiration exhibited a strong seasonal pattern, with the highest rates found in the warm and wet growing season (April–September) and the lowest rates in the dry dormant season (December–February). Soil respiration rates showed a significant positive exponential relationship with soil temperature, whereas soil moisture only affect soil respiration at dry conditions in the dormant season. Annual accumulative soil respiration was 601±30 g CO 2 ‐C m −2 yr −1 in the Controls. Annual mean soil respiration rate in the Control, Low‐N and Medium‐N treatments (69±3, 72±3 and 63±1 mg CO 2 ‐C m −2 h −1 , respectively) did not differ significantly, whereas it was 14% lower in the High‐N treatment (58±3 mg CO 2 ‐C m −2 h −1 ) compared with the Control treatment, also the temperature sensitivity of respiration, Q 10 was reduced from 2.6 in the Control with 2.2 in the High‐N treatment. The decrease in soil respiration occurred in the warm and wet growing season and were correlated with a decrease in soil microbial activities and in fine root biomass in the N‐treated plots. Our results suggest that response of soil respiration to atmospheric N deposition in tropical forests is a decline, but it may vary depending on the rate of N deposition.

Nitrate leaching from three afforestation chronosequences on former arable land in Denmark - KARIN HANSEN; LARS ROSENQVIST; LARS VESTERDAL; PER GUNDERSEN (Global Change Biology, 2007)
In regions dominated by agricultural activities, nitrogen (N) is recognized as a major pollutant in aquatic environments. In north‐western Europe, afforestation of agricultural land is part of a strategy to improve water quality. In Denmark, former arable land has been afforested during the past 40–50 years. This study evaluated the effect of afforestation of former arable land on nitrate leaching, based on three afforestation chronosequences. Precipitation, canopy throughfall and soil water were collected and soil moisture was monitored at two Danish locations, Vestskoven (nutrient‐rich, medium deposition) and Gejlvang (nutrient‐poor, high deposition). Afforestation was performed using Norway spruce [ Picea abies (Karst.) L.] and common oak ( Quercus robur L.) at Vestskoven and Norway spruce at Gejlvang. The results suggest that afforestation of former arable land initially leads to lower nitrate leaching than that occurring under the former agricultural land use, and largely below the standard of 50 mg NO − 3 L −1 for groundwater to be utilized as drinking water. Nitrate concentrations became almost negligible in forest stands of 5–20 years of age. However, after canopy closure (>20 years) nitrate concentrations below the root zone and nitrate leaching tended to increase. This was attributed to increased N deposition with increasing canopy development and decreased N demand once the most N‐rich biomass compartments had been built up. Nitrate leaching started to increase at a throughfall deposition level of about 10 kg N ha −1 yr −1 . Compared with nutrient‐poor sandy soils, nutrient‐rich clayey soils appeared more vulnerable to disturbance of the N cycle and to increased N deposition, leading to N saturation and enhanced nitrate leaching. In approximately the first 35 years after afforestation, nitrate leaching below the root zone was generally higher below oak than below Norway spruce.

The impact of nitrogen deposition on carbon sequestration in European forests and forest soils - WIM DE VRIES; GERT JAN REINDS; PER GUNDERSEN; HUBERT STERBA (Global Change Biology, 2006)
An estimate of net carbon (C) pool changes and long‐term C sequestration in trees and soils was made at more than 100 intensively monitored forest plots (level II plots) and scaled up to Europe based on data for more than 6000 forested plots in a systematic 16 km × 16 km grid (level I plots). C pool changes in trees at the level II plots were based on repeated forest growth surveys At the level I plots, an estimate of the mean annual C pool changes was derived from stand age and available site quality characteristics. C sequestration, being equal to the long‐term C pool changes accounting for CO 2 emissions because of harvest and forest fires, was assumed 33% of the overall C pool changes by growth. C sequestration in the soil were based on calculated nitrogen (N) retention (N deposition minus net N uptake minus N leaching) rates in soils, multiplied by the C/N ratio of the forest soils, using measured data only (level II plots) or a combination of measurements and model calculations (level I plots). Net C sequestration by forests in Europe (both trees and soil) was estimated at 0.117 Gton yr −1 , with the C sequestration in stem wood being approximately four times as high (0.094 Gton yr −1 ) as the C sequestration in the soil (0.023 Gton yr −1 ). The European average impact of an additional N input on the net C sequestration was estimated at approximately 25 kg C kg −1 N for both tree wood and soil. The contribution of an average additional N deposition on European forests of 2.8 kg ha −1 yr −1 in the period 1960–2000 was estimated at 0.0118 Gton yr −1 , being equal to 10% of the net C sequestration in both trees and soil in that period (0.117 Gton yr −1 ). The C sequestration in trees increased from Northern to Central Europe, whereas the C sequestration in soil was high in Central Europe and low in Northern and Southern Europe. The result of this study implies that the impact of forest management on tree growth is most important in explaining the C pool changes in European forests.

Seven days’ around the clock exhaustive physical exertion combined with energy depletion and sleep deprivation primes circulating leukocytes - Yngvar Gundersen; Per Kristian Opstad; Trine Reistad; Ingjerd Thrane; Per Vaagenes (European Journal of Applied Physiology, 2006)

Soil CN ratio as a scalar parameter to predict nitrous oxide emissions - Leif Klemedtsson; Karin Von Arnold; Per Weslien; Per Gundersen (Global Change Biology, 2005)
Forested histosols have been found in some cases to be major, and in other cases minor, sources of the greenhouse gas nitrous oxide (N 2 O). In order to estimate the total national or global emissions of N 2 O from histosols, scaling or mapping parameters that can separate low‐ and high‐emitting sites are needed, and should be included in soil databases. Based on interannual measurements of N 2 O emissions from drained forested histosols in Sweden, we found a strong negative relationship between N 2 O emissions and soil CN ratios ( r 2 adj =0.96, mean annual N 2 O emission= a e (− b CN ratio) ). The same equation could be used to estimate the N 2 O emissions from Finnish and German sites based on CN ratios in published data. We envisage that the correlation between N 2 O emissions and CN ratios could be used to scale N 2 O emissions from histosols determined at sampled sites to national levels. However, at low CN ratios (i.e. below 15–20) other parameters such as climate, pH and groundwater tables increase in importance as regulating factors affecting N 2 O emissions.

Factors affecting swimming economy in children and adults - Per-Ludvik Kjendlie; Frank Ingjer; Robert Keig Stallman; James Stray-Gundersen (European Journal of Applied Physiology, 2004)

Passive and active floating torque during swimming - Per-Ludvik Kjendlie; Robert Keig Stallman; James Stray-Gundersen (European Journal of Applied Physiology, 2004)

Soil Solution Chemistry and Element Fluxes in Three European Heathlands and Their Responses to Warming and Drought - Inger K. Schmidt; Albert Tietema; Dylan Williams; Per Gundersen; Claus Beier; Bridget A. Emmett; Marc Estiarte (Ecosystems, 2004)

Novel Approaches to Study Climate Change Effects on Terrestrial Ecosystems in the Field: Drought and Passive Nighttime Warming - Claus Beier; Bridget Emmett; Per Gundersen; Albert Tietema; Josep Peuelas; Marc Estiarte; Carmen Gordon; Antonie Gorissen; Laura Llorens; Ferran Roda; Dylan Williams (Ecosystems, 2004)

Adults have lower stroke rate during submaximal front crawl swimming than children - Robert Keig Stallman; James Stray-Gundersen; Per-Ludvik Kjendlie (European Journal of Applied Physiology, 2004)

Differences in the energy cost between children and adults during front crawl swimming - Per-Ludvik Kjendlie; Frank Ingjer; rjan Madsen; Robert Keig Stallman; James Stray-Gundersen (European Journal of Applied Physiology, 2004)

Throughfall Nitrogen Deposition Has Different Impacts on Soil Solution Nitrate Concentration in European Coniferous and Deciduous Forests - Hanne L. Kristensen; Per Gundersen; Ingeborg Callesen; Gert Jan Reinds (Ecosystems, 2004)

Changes in soil properties after afforestation of former intensively managed soils with oak and Norway spruce - Eva Ritter; Lars Vesterdal; Per Gundersen (Plant and Soil, 2003)